By changing the independent variable.solve the differential equation. d2x/dx2 - (dy/dx)(1/x) + 4x2y = x4
Let "t=x^2,x=\\sqrt{t}"
"y''-y'\/(\\sqrt{t})+4yt=t^2"
"\\frac{dy}{dx}=2\\sqrt{t}\\frac{dy}{dt},\\frac{d^2y}{dx^2}=4t\\frac{d^2y}{dt^2}+2\\frac{dy}{dt}"
"4t\\frac{d^2y}{dt^2}+4ty(t)=t^2"
"\\frac{d^2y}{dt^2}+y(t)=t\/4"
"k^2+1=0"
"k=\\pm i"
The general solution:
"y(t)=c_1cost+c_2sint"
For the particular solution:
"\\tilde{y}(t)=A+Bt"
Then:
"A+Bt=t\/4"
"A=0,B=1\/4"
"\\tilde{y}(t)=t\/4"
So:
"y(t)=t\/4+c_1cost+c_2sint"
Answer:
"y(x)=x^2\/4+c_1cos(x^2)+c_2sin(x^2)"
Comments
Leave a comment